A modular scalable approach to occlusion-robust low-latency optical tracking - Köpfle, Andreas; Schwarz, Markus; Pott, Peter Paul; Wagner, Achim; Männer, Reinhard; Badreddin, Essameddin; Scharf, Hanns-Peter (Medical image computing and computer-assisted intervention - MICCAI 2004, 2004)
An advanced optical tracking system for computer assisted surgery (CAS) is presented. The system supports an arbitrary number of cameras that may be placed at suitable positions e.g. fixed cameras at the ceiling of the operating theater or movable cameras on the operating lamps. The modular scalable system architecture reduces occlusion problems and allows adaptation to tracking scenarios of different complexity. The camera modules each integrate hardware-based image processing to allow for low latency of 10ms required in demanding applications like robot control. As a first application tracking of a handheld robotic manipulator has been implemented.